Associação entre depressão e saúde bucal em gestantes: estudo transversal aninhado à coorte BRISA - Menêzes, Cláudia Régia de Souza Dias de (2016)
This thesis aimed to investigate the association between depression and oral health in pregnant women. This was a cross-sectional study nested in the cohort "etiological factors of preterm birth and consequences of perinatal factors in child health: birth cohorts in two Brazilian cities – BRISA". In this study only the data of São Luís were taken into account. Depression was assessed using Population Screening Scale for Depression of the Center for Epidemiologic Studies Depression Scale. We evaluated the following oral health parameters: number of decayed, missing and filled, visible plaque index, Bleeding on Probing index and Clinical Probing Depth. Under the proposed causal model, the association of depression and oral outcomes was estimated by prevalence ratios in Poisson regression analysis with adjustment for confounders proposed by the analising of the Directed Acyclic Graphs. There was an association between depression and the number of decayed teeth and teeth indicated for extraction both by the total effect model adjusted for age, education, income and frequency of consumption of soft drinks, chocolaty drinks and bakery sweets / biscuits / cakes (PR = 1.15; 95% CI 1:02 to 1:29; p = 0.001) as well as the direct effects model adjusted for age, education, income, soft drink consumption frequency, chocolaty beverage, bakery sweets / biscuits / cakes / and biofilm (PR = 1.18; 95% CI 01.05 -1.33, p = 0.005). Severe symptoms of depression were not associated with the number of teeth with CPD≥4mm and BOP at the same place in both the total effect model adjusted for age, education, income and obesity (PR = 1:00; 95% CI: 0.86- 1:17; p = 0.94) as well as the direct effects model adjusted for age, consumption of alcohol, smoking, diabetes, hypertension, obesity and dental biofilm (PR = 1.5; 95% CI 0.90-1.22; 00:50). Severe symptoms of depression appear to be associated with dental caries in pregnant women, but not with periodontal disease.